The Influence of Solvent on Complex Formation of Crown Ether with Tetraphenylphosphonium Chloride - Tripathi, Atri Deo (Journal of Applied Solution Chemistry and Modeling, 2015)
The host guest interactions of crown ether (18-C-6) with tetraphenylphosphonium chloride (TPPC) were studied in different solvents at 303.15 K. The values of reaction enthalpies, ΔH0, and equilibrium constant, K, have been calculated and the results show that solvation of tetraphenylphosphonium ion (Ph4P+) is not very important. Because the cavity of the 18-C-6 is too small to completely accommodate large Ph4P+ ion. Thus, the interactions between the cation and the oxygen donor atoms of the ligand decrease, the large cation is surrounded by large organic moieties which interact more strongly with the organic environment and therefore it will not have tendency to form complex in non-aqueous solvents.